Cytokinin oxidase/dehydrogenase genes in barley and wheat: cloning and heterologous expression - Galuszka, Petr; Frébortová, Jitka; Werner, Tomás; Yamada, Mamoru; Strnad, Miroslav; Schmülling, Thomas; Frébort, Ivo (European journal of biochemistry, 2004)
The cloning of two novel genes that encode cytokinin oxidase/dehydrogenase (CKX) in barley is described in this work. Transformation of both genes into Arabidopsis and tobacco showed that at least one of the genes codes for a functional enzyme, as its expression caused a cytokinin-deficient phenotype in the heterologous host plants. Additional cloning of two gene fragments, and an in silico search in the public expressed sequence tag clone databases, revealed the presence of at least 13 more members of the CKX gene family in barley and wheat. The expression of three selected barley genes was analyzed by RT-PCR and found to be organ-specific with peak expression in mature kernels. One barley CKX (HvCKX2) was characterized in detail after heterologous expression in tobacco. Interestingly, this enzyme shows a pH optimum at 4.5 and a preference for cytokinin ribosides as substrates, which may indicate its vacuolar targeting. Different substrate specificities, and the pH profiles of cytokinin-degrading enzymes extracted from different barley tissues, are also presented.
Keywords: Nicotiana; sekvenční seřazení; Cytokinins; 2,6-Dichloroindophenol; exprese genu; Benzoquinones; sekvenční homologie aminokyselin; Gene Expression; Hordeum; Substrate Specificity; Sequence Homology, Amino Acid; Molecular Sequence Data; klonování DNA; 2,6-dichlorindofenol; molekulární sekvence - údaje; geneticky modifikované rostliny; sekvence aminokyselin; pšenice; Recombinant Proteins; Arabidopsis; oxidoreduktasy; Amino Acid Sequence; rostlinné geny; rekombinantní proteiny; Genes, Plant; Plants, Genetically Modified; substrátová specifita; tabák; Hydrogen-Ion Concentration; Sequence Alignment; Triticum; ječmen (rod); benzochinony; Cloning, Molecular; koncentrace vodíkových iontů; Oxidoreductases; cytokininy